Juridical Analysis of Cyber Crime Offenses in Hacking Hospital Management Information Systems (SIMRS) - Sidi, Redyanto (Faculty of Law, Universitas Pekalongan, 2024)
In the current digital era, the increasing reliance on information technology in the healthcare sector, especially through the use of Hospital Management Information Systems (SIMRS) as an effort for administrative orderliness and also to avoid medical disputes in health services, brings significant risks related to cybercrime. SIMRS, which integrates the management of sensitive health data such as medical records and financial information, has become a primary target for cybercriminals. Cybercrime, particularly hacking, is a real threat that not only disrupts hospital operations but also damages public trust in the healthcare system and threatens the loss or misuse of data. This study aims to identify the legal vulnerabilities in SIMRS in Indonesia, analyze the legal implications of cybercrime hacking, and evaluate the effectiveness of existing regulations against hacking as an evaluation and protection for the present and the future. The research method used is doctrinal, focusing on the normative analysis of relevant regulations and legal documents, including the Indonesian Law No. 11 of 2008 as amended by Indonesian Law No. 19 of 2016 on Information and Electronic Transactions, and the Minister of Health Regulation of the Republic of Indonesia No. 82 of 2013 on Hospital Management Information Systems. This approach involves data collection through literature studies and analysis of existing regulations to identify gaps and the need for legal reforms. The results of the research show that although the ITE Law provides a strong legal foundation, there is still a need for revision and adaptation to accommodate technological developments and the ever-changing hacking practices. Based on these findings, the recommendations proposed include revising the ITE Law to include more specific aspects of health data security, adopting international cybersecurity standards, enhancing human resource capacity, and fostering closer cooperation between sectors in developing cybersecurity solutions. The implementation of these recommendations is expected to strengthen data security in SIMRS and improve the resilience of the health sector against cyber threats. Thus, the integrity and privacy of patient data can be maintained, ensuring smooth hospital operations.